2015
DOI: 10.1177/2047981614546795
|View full text |Cite
|
Sign up to set email alerts
|

Possible confounding factors on cerebral diffusion tensor imaging measurements

Abstract: BackgroundDiffusion tensor imaging (DTI) is prone to numerous systemic confounding factors that should be acknowledged to avoid false conclusions.PurposeTo investigate the possible effects of age, gender, smoking, alcohol consumption, and education on cerebral DTI parameters in a generally healthy homogenous sample with no neurological or psychiatric diseases.Material and MethodsForty (n = 40) subjects (mean age, 40.3 years; SD, 12.3) underwent brain DTI with 3 T magnetic resonance imaging (MRI). At enrolment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 42 publications
2
9
3
Order By: Relevance
“…In contrast, in our study, the freehand method gave a slightly higher variation in the corpus callosum than the circle method in previous studies (13,41). This may also be due to the fact that in our study, ROIs were plotted on the axial image, whereas in previous studies they were plotted on the sagittal image (13,41). Thus, in this particular region, it would be better to use the circle method for a sagittal image than the freehand method for an axial image.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast, in our study, the freehand method gave a slightly higher variation in the corpus callosum than the circle method in previous studies (13,41). This may also be due to the fact that in our study, ROIs were plotted on the axial image, whereas in previous studies they were plotted on the sagittal image (13,41). Thus, in this particular region, it would be better to use the circle method for a sagittal image than the freehand method for an axial image.…”
Section: Discussioncontrasting
confidence: 99%
“…Speci cally, in the youngest age group, the FA values were higher and the RD values lower in the frontobasal area in both hemispheres when compared to the other age groups. For FA, this result has already been published in our previous study (41). Other studies have also found changes in the frontal regions of the brain caused by aging (16,17).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations